CHOLECYSTECTOMY BY THE MINIMAL-ACCESS APPROACH: MINILAPAROTOMY AND LAPAROSCOPY - NISHINA, Takuya; MANABE, Kohji; GOTOH, Kiyotoshi; KAWAGUCHI, Kenji; OHNO, Satoshi; ARATA, Atushi; MAKINO, Yasuhiro; KOBAYASHI, Gensoh; TAKEUCHI, Hitoshi; KONAGA, Eiji; KANAOKA, Yuji; KASHITANI, Masaaki; et al. (Japanese Journal of National Medical Services, 1991)
There is a tendency to limit the operative scars as small as possible nowadays and to reduce patient's physical and psychological pain. We analysed 13 patients; 3 managed by minil aparotomy, and 10 by laparoscopic cholecystectomy (LSC). The length of skin incision in minilaparotomy was longer according to the obesity index. There was no significant difference between the two methods in operative time. The patients were offered less pain, faster recovery, and improved cosmetic results by the seprocedures, especially by LSC. Complication occurred in one case of LSC. To avoidserious comprications, it is most important to decide the indication properly with imaging diagnosis, and to convert to open cholecystetomy early in difficult cases.